An analysis of the English textbook “think” to the curriculum 2013 - Fina Sakinah Mawaddah; Farida Hamid; Syauki Syauki (STABN RADEN WIJAYA WONOGIRI, 2023)
The study aimed to evaluate the relevance of materials in the textbook